The Developmental Stages of An Accumulative Cone of Dry Valley as an Indication of Change in Natural Environment Conditions (Western Pomerania) - Paluszkiewicz, Renata (Quaestiones Geographicae, 2013)
The aim of this paper is to present the stages of development of an alluvial cone as an indication of change in natural environment conditions. a detailed research was conducted within the upland regions of Drawsko Lakeland. At the valley mouth of one of the erosional-denudational valleys an alluvial cone in question splays out. The imparity between the capacity of the erosional-denudational valley and the capacity of the alluvial cone indicates that the main stage of erosion had taken place before the cone’s deposition. During the beginning stage the material acquired from the dissection was most likely delivered directly to the channel of Dębnica river and was incorporated in the fluvial transport. The cone was formed during the later stage. The results of the radiocarbon analyses reveal that the formation of the alluvial cone and the valley associated with the cone took place during the Subatlantic. It was also estimated that the cone aggraded with the rate of approximately 3,9 mm per year